Glaucoma Disease: A Survey - Masood, Saleha; Sharif, Muhammad; Raza, Mudassar; Yasmin, Mussarat; Iqbal, Muhammad; Younus Javed, Muhammad (Current Medical Imaging, 2015)
Glaucoma is a neurodegenerative disease and is considered as one of the most common reasons of blindness. Degeneration of nerves is an irreversible process so early diagnosis of this disease is inevitable to avoid permanent loss of vision. Diagnosis of glaucoma usually consists of inspection of the structural deterioration of nerve in conjunction with the examination of visual function. This article presents a detailed overview of glaucoma, its symptoms and the potential it has to affect the persons. The research work related to its diagnosis and treatment is also reviewed in this article.
Keywords: Pattern matching